Analysis for negative line loss, higher voltage at downstream node and active and reactive components of capacitor current. (3rd April 2018) - Paul, Sushanta
Abstract: In IEEE's load flow simulation results for 13-bus system, 34-bus system and 123-bus system, it was found that line losses in some feeders are negative. In a study, it was also found that, the voltage at the downstream node is higher than the voltage at the upstream node, even though all the current flows from the upstream node to the downstream node. In this paper, it has been analysed how negative line losses in a phase and higher voltage at the downstream node appear in an ac power system. It has also been demonstrated that even though capacitor generates only reactive power, its current has both active and reactive components with respect to the system reference.